Formulations of Amlodipine: A Review. (16th October 2016) - Sheraz, Muhammad Ali; Ahsan, Syed Furqan; Khan, Marium Fatima; Ahmed, Sofia; Ahmad, Iqbal
Abstract : Amlodipine (AD) is a calcium channel blocker that is mainly used in the treatment of hypertension and angina. However, latest findings have revealed that its efficacy is not only limited to the treatment of cardiovascular diseases as it has shown to possess antioxidant activity and plays an important role in apoptosis. Therefore, it is also employed in the treatment of cerebrovascular stroke, neurodegenerative diseases, leukemia, breast cancer, and so forth either alone or in combination with other drugs. AD is a photosensitive drug and requires protection from light. A number of workers have tried to formulate various conventional and nonconventional dosage forms of AD. This review highlights all the formulations that have been developed to achieve maximum stability with the desired therapeutic action for the delivery of AD such as fast dissolving tablets, floating tablets, layered tablets, single-pill combinations, capsules, oral and transdermal films, suspensions, emulsions, mucoadhesive microspheres, gels, transdermal patches, and liposomal formulations.